The impact of semester-abroad experiences on post-sojourn L2 motivation - Du, Xujia (Studies in Second Language Learning and Teaching, 2019)
Numerous studies have examined sojourners’ L2 motivation during their stay abroad. Much remains unknown about the impact of study abroad (SA) experiences on their L2 motivation after they return to the home environment. This study tracked the English learning motivation of three Chinese university students from immediately after their semester-long exchange program in an English-speaking country until six months after the sojourn. The participants were requested to complete a questionnaire and took part in an interview immediately following their re-entry and another interview six months later. The participants’ post-sojourn English learning motivation was influenced by their L2 selves and the context they were situated in. The motivational capacity of SA experiences was manifested in its profound impact on the participants’ ideal L2 self-images. Satisfactory SA experiences contributed to an ideal L2 self with higher L2 proficiency and international posture, whereas unsatisfactory experiences led to a lessening role of L2 in the participants’ future work and life. The findings also reveal that the participants’ understandings of both their positive and negative SA experiences became fossilized after the sojourn. Some practical implications were discussed for higher education institutions to optimize the post-sojourn motivational impact of SA programs.